Characterization of glyphosate‐resistant Burkholderia anthina and Burkholderia cenocepacia isolates from a commercial Roundup® solution. Issue 1 (16th November 2021) - Hertel, Robert; Schöne, Kerstin; Mittelstädt, Carolin; Meißner, Janek; Zschoche, Nick; Collignon, Madeline; Kohler, Christian; Friedrich, Ines; Schneider, Dominik; Hoppert, Michael; Kuhn, Ramona; Schwedt, Inge; et al.
Summary: Roundup® is the brand name for herbicide solutions containing glyphosate, which specifically inhibits the 5‐enolpyruvyl‐shikimate‐3‐phosphate (EPSP) synthase of the shikimate pathway. The inhibition of the EPSP synthase causes plant death because EPSP is required for biosynthesis of aromatic amino acids. Glyphosate also inhibits the growth of archaea, bacteria, Apicomplexa, algae and fungi possessing an EPSP synthase. Here, we have characterized two glyphosate‐resistant bacteria from a Roundup solution. Taxonomic classification revealed that the isolates 1CH1 and 2CH1 are Burkholderia anthina and Burkholderia cenocepacia strains respectively. Both isolates cannot utilize glyphosate as a source of phosphorus and synthesize glyphosate‐sensitive EPSP synthase variants. Burkholderia . anthina 1CH1 and B . cenocepacia 2CH1 tolerate high levels of glyphosate because the herbicide is not taken up by the bacteria. Previously, it has been observed that the exposure of soil bacteria to herbicides like glyphosate promotes the development of antibiotic resistances. Antibiotic sensitivity testing revealed that the only the B . cenocepacia 2CH1 isolate showed increased resistance to a variety of antibiotics. Thus, the adaptation of B . anthina 1CH1 and B . cenocepacia 2CH1 to glyphosate did not generally increase the antibiotic resistance of both bacteria. However, our study confirms the genomic adaptability of bacteria belonging to the genus Burkholderia .